Analisis Yuridis Hak Berserikat Pekerja Berdasarkan Undang-undang Nomor 13 Tahun 2003 tentang Ketenagakerjaan - Huda, Miftahul; Mulyanto, Mulyanto (Lembaga Dakwah dan Pembangunan Masyarakat Universitas Cokroaminoto Yogyakarta (LDPM UCY), 2025)
Constitutional and legal protection in Indonesia guarantees workers' freedom to form unions, a fundamental human right. This paper aims to draw conclusions by examining the regulation and implementation of workers' right to organize through the perspective of Indonesian labor legislation, namely Law No. 13 of 2003 concerning Manpower, including the obstacles to its implementation. This research utilizes primary, secondary, and tertiary legal sources obtained through a literature review to conduct normative legal research using a juridical and conceptual approach. Based on the findings, the right to organize in Indonesia has a strong basis in international and national law, including the conformity with Law No. 98. However, problems such as forced union dissolution, workers' lack of insight, and weak enforcement of labor laws hinder the implementation of this right. To ensure the effective and fair implementation of the right to organize, increased government support, law enforcement, and union capacity are essential.